Sex steroid levels and breeding performance of F1 generation Malaysian mahseer, Tor tambroides (Bleeker, 1854) by removal of dopaminergic inhibition - Nik Daud, Nik Md. Azuadi; Siraj, Siti Shapor; Daud, Siti Khalijah; Christianus, Annie; Harmin, Sharr Azni; Sungan, Stephen; Britin, Raymond (Academic Journals, 2013)
Induced ovulation of captive Malaysian mahseer (Tor tambroides) often encounters low reproductive performances. The present study was conducted to gain insight to problems associated with poor breeding performance of Malaysian mahseer in captivity. In this study, sex steroid hormone levels and ovulation performance in filial 1 (F1) generation of Malaysian mahseer (Tor tambroides) were investigated. Fishes were injected with ovatide, combination of Salmon Gonadotropin Releasing Hormone Analogue (sGnRHa), DOM, sGnRHa+DOM and 0.9% NaCl. A total of 30 matured females T. tambroides with weight ranged from 2.01-3.80 kg were used in this study. The females were given ovaplant (39.5-37.3 μg kg-1) pretreatment for 6 weeks prior to hormones injection. Females were given a single intramuscular injection of ovatide (0.5 mL kg-1 b.wt.), sGnRHa (10 μg kg-1 b.wt.), DOM (5 mg kg-1 b.wt.), sGnRHa+DOM (10 μg kg-1 b.wt.+5 mg kg-1 b.wt.) or 0.9% NaCl. Blood samples were collected at 0, 6, 12 and 24 h (s) after injection. The effect of these treatments on sex steroids level (Testosterone (T) and 17β-Estradiol (E2) and ovulation performance of F1 Tor tambroides were evaluated. Result showed that higher ovulatory response was observed in the group treated with positive control ovatide (0.5 mL kg-1 b.wt.). Interestingly, it was observed that sGnRHa and Domperidone (DOM) produce highest egg and larval qualities compared to ovatide and sGnRHa alone. No ovulation occurred in the group treated with DOM alone. Sex steroids plasma concentration of T and E2 increased significantly in association with ovulation. The levels fluctuated and reached a peak at 12 h, then dropped dramatically at 24 Post Injection (PI). In contrast the non-ovulated groups, the sex steroids hormone concentration showed little increment after injection and rose at 12 h PI, then slowly dropped at 24 h pi. These results provide evidence for a strong dopamine inhibition on GtH secretion in captive mahseer.